Revealing the Accountability of Tadulako University as a Step to Realizing Sustainable Development Goals - JURANA, Jurana; BAKRY, Mohammad Iqbal; INDRIASAR, Rahayu; PARWATI, Ni Made Suwitri; MAPPARESSA, Nurlela; RIDWAN, Muhammad (PT Keberlanjutan Strategis Indonesia, 2024)
This research aims to reveal the accountability of Tadulako University's 'tadulako-ness'. This research was conducted to reveal the accountability of the Tadulako University higher education institution for its various Tadulako activities in various fields related to achieving the goals and targets of the Sustainable Development Goals (SDGs). This is important to reveal the accountability of Tadulako University as the highest and largest educational institution in Central Sulawesi. Tadulako University's involvement during this pandemic is important to know considering that the philosophy of the name 'tadulako' used contains an important and deep meaning, namely the foundation of origin or leadership so that Tadulako University's involvement in carrying out its functions and activities is certainly very necessary. This research supports and is in line with the 17 Goals and 169 targets of the Sustainable Development Goals (SDGs). This is because the initial findings of this research are in the form of Tadulako University's concept of 'keadulakoan' accountability which is the basis and value as a reference for carrying out its accountability and aligning it with the vision and mission of Tadulako University as a form of implementing sustainable development goals. This research uses a descriptive approach. Data collection is carried out by collecting various data available in various existing reporting forms. The data was then analyzed in the context of the ketadulakoan philosophy. The results of the research show that disclosures regarding the character of ketadulakaon have not been fully revealed.